2005
DOI: 10.1517/17425255.1.3.399
|View full text |Cite
|
Sign up to set email alerts
|

Novel mechanisms of nonsteroidal anti-inflammatory drug-induced renal toxicity

Abstract: The exact mechanism(s) of NSAID-induced nephrotoxicity remains unclear, but most theories centre on the initial inhibition of COX and the subsequent perturbation of the numerous actions of COX in the kidney. Since the nineteenth century no NSAIDs have been developed that are devoid of renal adverse effects, including the COX-2 selective inhibitors. Formation of renal eicosanoids from arachidonic acid is significantly increased in the presence of various stimuli, and metabolic degradation of arachidonic acid an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
11
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(12 citation statements)
references
References 53 publications
1
11
0
Order By: Relevance
“…Several research studies developed over the past 15 years reported the evidence of NSAIDs-induced kidney dysfunctions, such as acute renal failure and electrolyte imbalance. Nonetheless, the exact mechanism(s) of nephrotoxicity remains still unclear, though most theories focus on the initial inhibition of the cyclooxygenase (COX), the enzyme involved in prostaglandins (PG) synthesis, producing vasoconstriction and the subsequent perturbation of the numerous actions of COX in the kidney [30]. …”
Section: Discussionmentioning
confidence: 99%
“…Several research studies developed over the past 15 years reported the evidence of NSAIDs-induced kidney dysfunctions, such as acute renal failure and electrolyte imbalance. Nonetheless, the exact mechanism(s) of nephrotoxicity remains still unclear, though most theories focus on the initial inhibition of the cyclooxygenase (COX), the enzyme involved in prostaglandins (PG) synthesis, producing vasoconstriction and the subsequent perturbation of the numerous actions of COX in the kidney [30]. …”
Section: Discussionmentioning
confidence: 99%
“…The use of NSAIDs is associated with various side effects, including gastrointestinal, renal, hepatic and allergic effects. [1][2][3][4] In addition, recent studies have shown that the benefits of NSAID use include the prevention of the development of colorectal cancer and Alzheimer's disease. [5,6] The pharmaceutical actions of all NSAIDs are believed to occur through the inhibition of prostaglandin (PG) synthesis by prostaglandin H synthase (PGHS), which is responsible for prostaglandin synthesis.…”
Section: Introductionmentioning
confidence: 99%
“…1 However the use of this drug has been implicated in some cases of nephrotoxicity. 2 Due to the importance of the assay of FFA for pharmaceutical formulations and biological fluids, several analytical methods have been developed for the quantitative determination of this drug in both pharmaceutical and biological samples.…”
Section: Introductionmentioning
confidence: 99%
“…The aim of the present contribution was to develop a simple and low-cost potentiometric flufenamate ISE immobilized in a graphite matrix (Pt Hg Hg 2 (FF) 2 Graphite, where FF stands for flufenamate ion) and to evaluate the applicability of this sensor to the determination of FFA in dosage forms and human serum samples.…”
Section: Introductionmentioning
confidence: 99%